Application of Pop-Up Book Media in Developing Children's Linguistic Intelligence - Diani Deka Rusanti; Naimah Naimah; Suyadi Suyadi; Khamim Zarkasih Putro (STAI Hubbulwathan Duri, 2023)
Pop-up books are very different from ordinary storybooks. Pop-up books are more modern when the pages are opened, they form three dimensions, and when closed, they become two dimensions so that children become interested in participating in learning activities using pop-up book media, especially in developing children's linguistic intelligence. This study aims to discover that pop-up book media can help develop children's linguistic intelligence. When opened into a three-dimensional image, Media designed to be a 900-shaped book can make children interested, happy, and active in expressing the language. This study uses a qualitative descriptive research with data collection carried out directly at the Primary Kindergarten location. Data collection tools used by researchers using observation, interviews, and documentation. The subjects in this study used 12 students, data analysis techniques used data reduction, data display and data verification. Learning activities with pop-up book media show the results that this activity can develop early childhood linguistic intelligence, which is shown that children are able to answer more complex questions, children are able to communicate orally without embarrassment, children already have an additional vocabulary, and the child can already understand the symbols in preparation for entering the next educational stage, namely calistung, the child can also retell today's activities.